'LIKE A LILY AMONGST THE THORNS': PATTERNS OF NOBLE POWER AND VIOLENCE BETWEEN FARNESE AND ORSINI, 1378–1447. (October 2019) - Luiten, Loek
Abstract : Violence and peace-making in medieval Italy have often been analysed in urban environments. But what happened if two powerful baronial families clashed in the countryside? This paper, by looking at the feud between the Farnese and Orsini di Pitigliano during the Western Schism, illuminates various patterns of conflict and conciliation. Such conflicts witnessed the participation of relatives, allies, and subjects who shared in the sense of community and honour of their lords. The various motivations for actors to become involved on behalf of or in opposition to barons are analysed here in detail. The events of the Farnese–Orsini feud on the micro-level are linked to wider developments on the Italian peninsula and European politics. In the second part of this paper the successful conclusion of the feud is analysed in light of the return of the papacy to Rome. The meticulous detail in which the peace agreement was hammered out then provides further insight into the strategies employed by baronial families to maintain the peace. In all, this paper therefore contributes to the study of violence and peace-making as well as of the Italian nobility during the fourteenth and fifteenth centuries. Abstract : I fenomeni di violenza e pacificazione nell'Italia medioevale sono stati spesso analizzati nel contesto urbano. Ma cosa succedeva quando due potenti famiglie baronali si scontravano nella campagna? Il presente contributo, attraverso l'analisi del caso del feudo tra i Farnese e gli Orsini di Pitigliano durante lo Scisma d'Occidente, illumina vari modelli di conflitto e di conciliazione. Questo tipo di conflitti vedeva la partecipazione di parenti, alleati e soggetti che condividevano un senso di comunità e onore dei loro signori. Le varie motivazioni che hanno spinto gli attori a intervenire in favore o in opposizione ai baroni sono analizzate in dettaglio. Gli eventi del feudo Farnese-Orsini sulla piccola scala sono connessi con i più ampi sviluppi della penisola italiana e della politica su scala europea. Nella seconda parte di questo articolo la conclusione favorevole delle vicende del feudo è analizzata alla luce del ritorno del papato a Roma. Il meticoloso dettaglio con cui il trattato di pace è stato elaborato fornisce elementi per comprendere le strategie utilizzate dalle famiglie baronali per mantenere la pace. In ultima analisi il presente studio contribuisce allo studio delle forme di violenza e pacificazione e contemporaneamente della nobiltà italiana durante i secoli XIV e XV.